'Preparation and characterization of high performance (Co, Cu)/Pt/γ‐Al2O3 bimetallic catalysts for oxidation of 2‐ propanol: Experiments and ANN modelling' by Darush Salari, Aligholi Niaei, Faezeh Aghazadeh, and Seyed Ali Hosseini. (21st April 2011) - Unknown
Abstract : The above article from The Canadian Journal of Chemical Engineering, published online on April 21, 2011 in Wiley Online Library (wileyonlinelibrary.com ), has been retracted by agreement between the authors, the journal's Editor in Chief, João B. P. Soares, and Wiley Periodicals, Inc. The retraction has been agreed due to unattributed overlap between this article and the following article published in the Journal of Environmental Science and Health Part A, 'Catalytic oxidation of 2‐Propanol over (Cr, Mn, Fe)‐Pt/γ ‐Al2 O3 bimetallic catalysts and modeling of experimental results by artificial neural networks' by A. Niaei, D. Salari, F. Aghazadeh, N. Çaylak, and A. Sepehrianazar, Volume 45, 2006, pages 454–463. REFERENCE [1] D. Salari, A. Niaei, F.Aghazadeh, S.A. Hosseini, "Preparation and characterization of high performance (Co, Cu)/Pt/γ‐Al2 O3 bimetallic catalysts for oxidation of 2‐propanol: Experiments and ANN modelling, " Can. J. Chem. Eng .2011, DOI:10.1002/cjce.20388 .